Cloud auditing best practices : perform security and IT audits across AWS, Azure, and GCP by building effective cloud auditing plans - Cambric, Shinesa; Ratemo, Michael (Packt Publishing, 2023)
Ensure compliance across the top cloud players by diving into AWS, Azure, and GCP cloud auditing to minimize security risks About This Audiobook Leverage best practices and emerging technologies to effectively audit a cloud environment Get better at auditing and unlock career opportunities in cloud audits and compliance Explore multiple assessments of various features in a cloud environment to see how it's done In Detail As more and more companies are moving to cloud and multi-cloud environments, being able to assess the compliance of these environments properly is becoming more important. But in this fast-moving domain, getting the most up-to-date information is a challenge--so where do you turn? Cloud Auditing Best Practices has all the information you'll need. With an explanation of the fundamental concepts and hands-on walk-throughs of the three big cloud players, this audiobook will get you up to speed with cloud auditing before you know it. After a quick introduction to cloud architecture and an understanding of the importance of performing cloud control assessments, you'll quickly get to grips with navigating AWS, Azure, and GCP cloud environments. As you explore the vital role an IT auditor plays in any company's network, you'll learn how to successfully build cloud IT auditing programs, including using standard tools such as Terraform, Azure Automation, AWS Policy Sentry, and many more. You'll also get plenty of tips and tricks for preparing an effective and advanced audit and understanding how to monitor and assess cloud environments using standard tools. By the end of this audiobook, you will be able to confidently apply and assess security controls for AWS, Azure, and GCP, allowing you to independently and effectively confirm compliance in the cloud. Audience This audiobook is for IT auditors looking to learn more about assessing cloud environments for compliance, as well as those looking for practical tips on how to audit them and what security controls are available to map to IT general computing controls. Other IT professionals whose job includes assessing compliance, such as DevSecOps teams, identity, and access management analysts, cloud engineers, and cloud security architects, will also find plenty of useful information in this audiobook. Before you get started, you'll need a basic understanding of IT systems and a solid grasp of cybersecurity basics.